2019
DOI: 10.3390/rs11212513
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Variations of Carbon Use Efficiency in Natural Terrestrial Ecosystems and the Relationship with Climatic Factors in the Songnen Plain, China

Abstract: The Songnen Plain (SNP) is an important grain production base, and is designated as an ecological red-line as a protected area in China. Natural ecosystems such as the ecological protection barrier play an important role in maintaining the productivity and sustainability of farmland. Carbon use efficiency (CUE), defined as the ratio of net primary productivity (NPP) to gross primary productivity (GPP), represents the ecosystem capacity of transferring carbon from the atmosphere to terrestrial biomass. The unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Studies have shown that LCLUC has a certain impact on climate and regional precipitation, and many scholars have carried out related studies in this regard [1][2][3]10,12]. Some scholars have analyzed the influence of cropland, forest, and urban change on precipitation in specific regions [13,14,17,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that LCLUC has a certain impact on climate and regional precipitation, and many scholars have carried out related studies in this regard [1][2][3]10,12]. Some scholars have analyzed the influence of cropland, forest, and urban change on precipitation in specific regions [13,14,17,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…LCLUC could affect the exchange of water, energy, greenhouse gases, non-greenhouse gases and aerosols between the land system and the atmosphere [10][11][12]. Albedo changes and greenhouse gas caused by these impacts will drive global climate change, while on a regional scale, the redistribution of energy and water vapor between land and atmosphere will contribute to regional climate change and affect precipitation distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of carbon use efficiency (CUE) of natural ecosystems in protected farmland areas is vital to predicting the impacts of natural and anthropogenic disturbances on carbon budgets and evaluating ecosystem functions. An article by Li et al [122] studied variations in the ecosystem CUE in the SNP using MODIS data products and the Carnegie-Ames-Stanford approach (CASA) model. The relationships revealed between the CUE and the phenological and climate factors helped explain the CUE of the natural ecosystems in the protected farmland areas and improved the understanding about the dynamics of ecosystem carbon allocation in temperate semi-humid to semi-arid transitional regions under climate and phenological fluctuations.…”
Section: Highlights Of the Special Issue Articlesmentioning
confidence: 99%
“…The understanding of carbon use efficiency (CUE) of natural ecosystems in protected farmland areas is vital to predicting the impacts of natural and anthropogenic disturbances on carbon budgets and evaluating ecosystem functions. An article by Li et al [122] studied variations in the ecosystem CUE in the SNP using MODIS data products and the Carnegie-Ames-Stanford approach (CASA) model. The relationships revealed between the CUE and the phenological and climate factors helped explain the CUE of the natural ecosystems in the protected farmland areas and improved the understanding about the dynamics of ecosystem carbon allocation in temperate semihumid to semi-arid transitional regions under climate and phenological fluctuations.…”
Section: Highlights Of the Special Issue Articlesmentioning
confidence: 99%